Home Public Services in Colombia: Its Provision, Regulation and Control - Matias Camargo, Sergio Roberto (Revista del CLAD Reforma y Democracia, 2015)
The home public services are a special category of public services, are irreplaceable assets, essential needs of the population, linked to the existence, quality and dignity of human life and fundamental rights accordingly. They are an economic activity and the Colombian model of provision, regulation and control is questioned. One socio legal and interdisciplinary approach, a theoretical method (analysis and synthesis) is used and documentary analysis was made.